2006
DOI: 10.1186/1477-3155-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microbial growth response to inorganic nanoparticles

Abstract: In order to enhance the utilization of inorganic nanoparticles in biological systems, it is important to develop a fundamental understanding of the influence they have on cellular health and function. Experiments were conducted to test silica, silica/iron oxide, and gold nanoparticles for their effects on the growth and activity of Escherichia coli (E. coli). Transmission electron microscopy (TEM) and dynamic light scattering (DLS) were used to characterize the morphology and quantify size distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 11 publications
3
40
0
2
Order By: Relevance
“…Biocompatible AuNPs were found to be efficient agent in cancer therapy [28]. Williams et al [29] reported that AuNPs used alone did not show antibacterial activity. However, AuNPs conjugated with antibiotics were found to improve antibiotic activity and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible AuNPs were found to be efficient agent in cancer therapy [28]. Williams et al [29] reported that AuNPs used alone did not show antibacterial activity. However, AuNPs conjugated with antibiotics were found to improve antibiotic activity and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…During this run, the nanospheres remained stable and showed little change in hydrodynamic radius. Stability of PEG coated gold particles in LB media has previously been observed as well [24]. …”
Section: A B Cmentioning
confidence: 99%
“…These experimentally obtained results indicate that PNIPAM coated CdTe QDs are a promising alternate to uncoated QDs. Coupled with the externally tunable dot distribution capabilities derived from the PNIPAM networks [22,24], this novel nanoplatform may be useful for combinatorial therapeutics. We are currently assessing optically modulated responses of several neuronal models to the bio-conjugated nanospheres.…”
Section: A B 4 Conclusionmentioning
confidence: 99%
See 2 more Smart Citations